Find gof and fog when f: R → R and g : R → R is defined by f(x) = 2x + x2 and  g(x) = x3

Asked by Sakshi | 1 year ago |  69

Solution :-

Given, f: R → R and g: R → R

so, gof: R → R and fog: R → R

f(x) = 2x + x2 and g(x) = x3

(gof) (x)= g (f (x))

= g (2x+x2)

= (2x+x2)3

Now, (fog) (x) = f (g (x))

= f (x3)

= 2 (x3) + (x3)2

= 2x+ x6

Answered by Aaryan | 1 year ago

Related Questions

Let A be the set of first five natural and let R be a relation on A defined as follows: (x, y) R x ≤ y

Let A be the set of first five natural and let R be a relation on A defined as follows: (x, y) R x ≤ y

Express R and R-1 as sets of ordered pairs. Determine also

(i) the domain of R‑1

(ii) The Range of R.

A function f: R → R is defined as f(x) = x3 + 4. Is it a bijection or not? In case it is a bijection, find f−1 (3).

A function f: R → R is defined as f(x) = x3 + 4. Is it a bijection or not? In case it is a bijection, find f−1 (3).

If f: R → R be defined by f(x) = x3 −3, then prove that f−1 exists and find a formula for f−1.

If f: R → R be defined by f(x) = x3 −3, then prove that f−1 exists and find a formula for f−1. Hence, find f−1 (24) and f−1 (5).

Consider f: R+ → [−5, ∞) given by f(x) = 9x2 + 6x − 5. Show that f is invertible with f-1(x) = $$\dfrac{\sqrt{(x+6)-1}}{3}$$
If f(x) = $$\dfrac{ (4x + 3)}{(6x – 4)}$$, x ≠ ($$\dfrac{2}{3}$$) show that fof(x) = x, for all x ≠ ($$\dfrac{2}{3}$$). What is the inverse of f?